Alteration of gut microbiota associated with hypertension in children - Sun, Jiahong; Yang, Liu; Ma, Chuanwei; Yang, Lili; Zhao, Min; Magnussen, Costan G.; Xi, Bo (BMC, 2025)
Background The association of disturbance in gut microbiota with hypertension (HTN) defined on three separate occasions among children and adolescents remains unclear. In this study, we aimed to compare the differences in gut microbiota composition and diversity between children with HTN and those with normal blood pressure (BP).
Methods Data and stool samples were collected from the second follow-up of a childhood cardiovascular health cohort study in 2021. 16 S ribosomal RNA gene sequencing was conducted to determine the relative abundance of microbial taxa in 51 children aged 10-14 years with HTN and 51 children with normal BP.
Results Compared with children with normal BP, those with HTN had decreased gut microbiome diversity. At the genus level, after adjusting for the false discovery rate (FDR), the proportions of several gut microbiota such as Blautia (P-FDR=0.042), Coprococcus (P-FDR=0.042), Eubacterium_ventriosum_group (P-FDR=0.027), Christensenellaceae_R-7_group (P-FDR=0.027), and norank_f__Lachnospiraceae (P-FDR=0.015) significantly decreased in children with HTN compared to those with normal BP. Receiver operating characteristic analysis, net reclassification improvement (NRI) and integrated discrimination improvement (IDI) were performed and showed that the genera norank_f__Lachnospiraceae and Dorea significantly enhanced the ability of body mass index to differentiate between children with HTN and those with normal BP (area under the receiver operating characteristic curve: 0.95, 95% confidence interval 0.91-0.99; NRI > 0; IDI = 0.12, P < 0.05). Phylogenetic Investigation of Communities by Reconstruction of Unobserved States showed that the mean proportions of cofactors and vitamins metabolism pathway and the glycan anabolism pathway were higher in children with HTN.
Conclusions Disturbances in the abundance and diversity of gut microbiota may contribute to the development of HTN in children. Gut microbiota biomarkers may be of significant importance in the early identification and diagnosis of childhood HTN.
Clinical trial number Not applicable.